THERMODYNAMIC ANALYSIS OF FE AND MG PARTITIONING BETWEEN PLAGIOCLASE AND SILICATE LIQUID - Sugawara T. (My University, 2000)
Thermodynamic analysis of Fe- and Mg-bearing plagioclase and silicate liquid was carried out based on reported element partitioning data between plagioclase and silicate liquid in reduced conditions, solution properties of ternary feldspar, standard state properties of plagioclase endmembers and solution properties of multicomponent silicate liquid. Derived mixing properties of Fe- and Mg-bearing plagioclase are in harmony with estimated results from synthetic experiments in the systems CaAl2Si2O8-CaFeSi3O8 and CaAl2Si2O8-CaMgSi3O8. Based on the determined solution properties of the plagioclase, a computer program to calculate the element partition relationships between Fe- and Mg-bearing plagioclase and multicomponent silicate liquid was developed. The FeO, MgO and MgO/(MgO + FeO) in plagioclase predicted from known liquid compositions and pressure are in agreement with measurements within 0.2 wt%, 0.1 wt% and 0.1 (mol ratio), respectively. The Fe3+ content in plagioclase crystallized at high oxygen fugacity can be estimated with this program. The Fe3+/total Fe ratio in plagioclase crystallized near the quartz-fayalite-magnetite buffer ranges from 0 to 0.5, which is consistent with previous study on natural plagioclase in submarine basalt. Derived solution properties of the Fe- and Mg-bearing plagioclase are also used to calculate equilibrium composition relationship between olivine and plagioclase. Change of XFo in olivine coexisting with plagioclase affects MgO and FeO contents in plagioclase greatly. The present model predicts XFo of coexisting olivine from the chemical composition of plagioclase to ±0.1 accuracy at given pressure and temperature.